The English language curriculum for petroleum students at Hadramout University of Science and Technology (HUST). - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)

(untitled)
Like all engineers, petroleum students need the English language to meet their academic and professional needs.